Associação da Expectativa do Paciente e Perda do Excesso de Peso Pós Cirurgia Bariátrica - Valente, Sibelie Souto (2020)
The obesity epidemic is a public health problem that calls for solution strategies in the scientific community, considering the treatment options, there is a significant increase in the number of bariatric surgeries in the world. Some patients do not achieve therapeutic success in the loss of excess body weight expected with bariatric surgery. Investigating the relationship between the patient's expectation variable and the outcome associated with excess weight loss is relevant for understanding psychological phenomena and cognitive structures that may be associated with the success or failure of the result of this procedure. The objective of this research was centered on knowing the association between the patient's expectation and the result of excess weight loss from bariatric surgery 2 years after surgery. The study had 132 participants and was based on the case-control methodology, considering cases, patients with therapeutic failure related to weight loss, after two years of bariatric surgery and control, patients with therapeutic success. Through the investigated variable, we sought to know information related to success and failure that would enable greater objectivity of decision making in the indication, clinical follow-up and the development of interventions tailored to the specific needs of patients. The results revealed that expectations related to the reduction of social prejudice and improvement of working conditions are associated with the unsatisfactory response to the expected excess weight loss in this surgical procedure. Failures in previous treatments for obesity control were identified as a favorable indicator related to success in weight loss after surgery.